2018
DOI: 10.1021/acs.inorgchem.8b01665
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Existing Criteria for the Prediction of Pyrochlore Formation and Stability

Abstract: Depending on intrinsic (e.g., radius ratio rule r/ r) and extrinsic factors (e.g., processing conditions), pyrochlore-type LnZrO oxides achieve variable degrees of structural disorder. We report on a systematic study of the structural and microstructural characteristics of the GdLn ZrO system, exploring the effect of replacing Gd with a wide range of homovalent lanthanide ions (Ln = Nd, Sm, Dy, Ho, Y, and Er; x = 0.20 and 0.80). All compositions were prepared via a mechanochemical reaction between the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 47 publications
3
39
0
1
Order By: Relevance
“…Reynolds et al (2013) studied the long-range structure of series members between the ordered pyrochlore Gd 2 Zr 2 O 7 and disordered fluorite Tb 2 Zr 2 O 7 . Fuentes et al (2018) probed similar zirconate oxides ( A x Gd 2-x Zr 2 O 7 ) and based on the experimental data of both studies, the phase boundary for the stability field of disordered fluorite occurs at ρ a ∼ 0.756. This agrees very well with work by Clements et al (2011) who investigated a solid solution of ordered Nd 2 Zr 2 O 7 and disordered Ho 2 Zr 2 O 7 and reported a critical transformation from ordered pyrochlore to disordered fluorite that corresponds, in our phase space calculated with univalent radii, to 0.757 < ρ a < 0.760.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Reynolds et al (2013) studied the long-range structure of series members between the ordered pyrochlore Gd 2 Zr 2 O 7 and disordered fluorite Tb 2 Zr 2 O 7 . Fuentes et al (2018) probed similar zirconate oxides ( A x Gd 2-x Zr 2 O 7 ) and based on the experimental data of both studies, the phase boundary for the stability field of disordered fluorite occurs at ρ a ∼ 0.756. This agrees very well with work by Clements et al (2011) who investigated a solid solution of ordered Nd 2 Zr 2 O 7 and disordered Ho 2 Zr 2 O 7 and reported a critical transformation from ordered pyrochlore to disordered fluorite that corresponds, in our phase space calculated with univalent radii, to 0.757 < ρ a < 0.760.…”
Section: Resultsmentioning
confidence: 98%
“…The ordered pyrochlore structure can be imagined as a 2 × 2 × 2 supercell of the fluorite unit cell in which the stoichiometric oxygen vacancy is ordered at a specific location creating distinct coordination polyhedra for the two cations: an 8-fold cubic polyhedron for the larger A-cation and a smaller 6-fold octahedron for the B-cation. The commonly used rule to explain or predict the boundary of the compositionally-induced transition between disordered fluorite ordered and ordered pyrochlore is when the ionic radius ratio of the 8-coordinated A-site cation (conventionally Shannon, 1976 ) and the 6-coordinated B-site cation exceeds 1.46 ( Subramanian et al, 1983 ; Minervini et al, 2000 ; Sickafus et al, 2000 ; Fuentes et al, 2018 ). Experimental and computational studies have shown that this ionic radius ratio is strongly correlated with the cation anti-site defect formation energy in A 2 B 2 O 7 ( Minervini et al, 2000 ; Sickafus et al, 2000 ) with an increased propensity for a disordered cation sublattice and a disordered fluorite structure for lower defect energies.…”
Section: Introductionmentioning
confidence: 99%
“…The instability of Ce 2 Zr 2 O 7+ z pyrochlores upon oxidation and the appearance of a domain structure can be related to the evolution of the R 2 Zr 2 O 7 pyrochlores upon decreasing the lanthanide size. The pyrochlore structure is stable if 1.46≲ r ≲1.80, r being the ratio of the R 3+ and Zr 4+ ionic radii in VIII and VI coordination, respectively . As r approaches the lower limit of 1.46, increasing disorder develops in the form of cation antisite defects and anion‐vacancy population, eventually leading to a fluorite phase.…”
Section: Discussionmentioning
confidence: 99%
“…This is an inherent source of strain in pyrochlore structures. The pyrochlore structure is usually described as an aniondeficient fluorite derivative structure with face-centred cubic ( fcc) stacking of alternating A 3 B and B 3 A metal atom layers parallel to the {111} fluorite planes (Subramanian et al, 1983;Fuentes et al, 2018;Trump et al, 2018). Both the A and B atoms form 3D kagomé arrays of anion-centred corner-connected tetrahedra, YA 4 and □B 4 (□ = vacancy) (Pannetier and Lucas, 1970) as shown in Fig.…”
Section: Pyrochlore Minerals and Htb-pyrochlore Intgergrowthsmentioning
confidence: 99%